What Is the Reality of Hiatal Hernia Management?—A Registry Analysis - Köckerling, Ferdinand; Zarras, Konstantinos; Adolf, Daniela; Kraft, Barbara; Jacob, Dietmar; Weyhe, Dirk; Schug-Pass, Christine (Frontiers in Surgery, 2020)
Introduction: To date, the guidelines for surgical repair of hiatal hernias do not contain any clear recommendations on the hiatoplasty technique with regard to the use of a mesh or to the type of fundoplication (Nissen vs. Toupet). This present 10-years analysis of data from the Herniamed Registry aims to investigate these questions. Methods: Data on 17,328 elective hiatal hernia repairs were entered into the Herniamed Registry between 01.01.2010 and 31.12.2019. 96.4% of all repairs were completed by laparoscopic technique. One-year follow-up was available for 11,280 of 13,859 (81.4%) patients operated during the years 2010–2018. The explorative Fisher's exact test was used for statistical calculation of significant differences with an alpha = 5%. Since the annual number of cases in the Herniamed Registry in the years 2010–2012 was still relatively low, to identify significant differences the years 2013 and 2019 were compared. Results: The use of mesh hiatoplasty for axial and recurrent hiatal hernias remained stable over the years from 2013 to 2019 at 20 and 45%, respectively. In the same period the use of mesh hiatoplasty for paraesophageal hiatal hernia slightly, but significantly, increased from 33.0 to 38.9%. The proportion of Nissen and Toupet fundoplications for axial hiatal hernia repair dropped from 90.2% in 2013 to 74.0% in 2019 in favor of “other techniques” at 20.9%. For the paraesophageal hiatal hernias (types II–IV) the proportion of Nissen and Toupet fundoplications was 68.1% in 2013 and 66.0% in 2019. The paraesophageal hiatal hernia repairs included a proportion of gastropexy procedures of 21.7% in 2013 and 18.7% in 2019. The recurrent hiatal hernia repairs also included a proportion of gastropexies 12.8% in 2013 and 15.1% in 2019, Nissen and Toupet fundoplications of 72.7 and 62.7%, respectively, and “other techniques” of 14.5 and 22.2%, respectively. No changes were seen in the postoperative complication and recurrence rates. Conclusion: Clear trends are seen in hiatal hernia repair. The use of meshes has only slightly increased in paraesophageal hiatal hernia repairs. The use of alternative techniques has resulted in a reduction in the use of the “classic” Nissen and Toupet fundoplication surgical techniques.